Large Mode Area Pr3+-Doped Chalcogenide PCF Design for High Efficiency Mid-IR Laser - Karin Ennser (IEEE Photonics Technology Letters, 2018)
We propose a novel design of a photonic crystal fiber made of praseodymium (Pr3+)-doped chalcogenide glass with single mode operation beyond 4 μm . Our design has an enlarged Pr3+-doped core diameter of 60 μm . The field area of the emitted fundamental mode is about 3160 μm2 at 4.5 μm and 2050 μm2 at a pump wavelength of 2.04 μm . This large mode field area not only reduces the nonlinear effects but also increases the possible pump power before the damage threshold. The selected laser layout avoids fabrication difficulties associated with cascaded fiber Bragg gratings in Pr3+-doped chalcogenide glass fibers. The proposed design also increases the laser efficiency by using the overlap of the emission cross sections of Pr3+ in the transitions (3F2, 3H6 → 3H5 and 3H5 → 3H4) to enable both transitions to simultaneously produce a single coherent mid-infrared wavelength. The simulation results reveal that more than 64% of slope efficiency could be achieved at 4.5 μm for a fiber loss of 1 dB/m.